Influence of the federal landowner Incentive Program - Sunni L. Carr; Steven P. Riley; Kristal Stoner; Gerry Steinauer; Thomas L. Walker Jr. (Wildlife Society Bulletin)
ABSTRACT The Landowner Incentive Program (LIP) was introduced as a federal conservation program administered by the U.S. Fish and Wildlife Service in 2002 as a means to incentivize private landowners in the management of rare wildlife species and their habitats. States and tribes were encouraged to apply for competitive funding and establish appropriate programs aimed at reversing population declines of wildlife species on privately owned land. We document the origin of LIP and highlight 2 case studies that exemplify innovations catalyzed by LIP. From 2002 to 2007, US$127 million was appropriated and >4,300 projects were completed nationwide. © 2019 The Wildlife Society.